A FLIFS (Festival Literário e Cultural de Feira de Santana) e a formação do leitor literário: a experiência do Colégio Estadual Reitor Edgard Santos - Lisboa, Marta Carvalho Ferreira (2023)
This study has the general objective of analyzing possible relationships between FLIFS (Feira de Santana Literary and Cultural Festival) and the formation of the literary reader, based on fruitful reading practices and artistic-literary manifestations proposed to Basic Education students at Colégio Estadual Reitor Edgard Santos. We understand as notable the growth in the number of literary events in Brazil and the consequent increase in book sales at these festivals where books are the main attraction. In this national scenario, the consolidation of FLIFS stands out, a festival held in the municipality of Feira de Santana, Bahia, for sixteen years, which projects itself as a cultural, democratic and literary space, aimed at the readership of a wide audience – including the school – as well as an event based on the development of discussions and actions aimed at public policies to promote reading for feira and bahia society. In this context, this study analyzes the cultural reading practices experienced by students at a public school in FLIFS to discuss how they can contribute to the formation of literary readers. From a theoretical point of view, this study is based on two main axes, reading and literature, which unfold into the following categories: conception of reading, literature and reader (YUNES, 1995; ABREU, 2006; CÂNDIDO, 2011; FREIRE , 2002; 2011; JOUVE, 2002, 2013; CASTRO, 2007); cultural literacy and reading practices (KLEIMAN, 2006; STREET, 2014; CHARTIER, 1999, 1989; ROJO, 2009, 2012); reader training, literary literacy (COSSON, 2006, 2014; ZILBERMAN, 1988; 2001; SILVA, 1998; YUNES, 2002; 2003); young reader profile (PETIT, 2009, 2010, 2013; SANTAELLA, 2004, 2014); public policies for reader training (PAULA, 2010; RIBEIRO, 2003). From a methodological point of view, a qualitative approach is used, from the perspective of social research, of the participant type, aiming to explain processes that occurred in the school environment and during the FLIFS, based on situations experienced by the collaborators, namely, twenty students of basic education, FLIFS attendees, who attend the final years of Elementary and High School at Colégio Estadual Reitor Edgard Santos, the locus of the study. The information was constructed using document analysis, semi-structured interviews and discussion groups, and the results were analyzed in the light of Discursive Textual Analysis (DTA). The results point to the relevant role of FLIFS in accessing literary books, enabling the construction of one's own collection, as well as the importance of continuous and interdisciplinary reading projects in the various stages of basic education for the process of training literature readers.